Gas separation membrane as well as preparation method and application thereof
By embedding silver nanowires in the PVAm film, the orderly rearrangement of the PVAm segments is disrupted, and the crystallization region formation problem caused by excessive primary amino content is solved, and the performance optimization of the PVAm film and the improvement of CO2 permeability are achieved.
Patent Information
- Application Number
- CN202510094871.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-01-21
AI Technical Summary
While the existing PVAm films increase the permeability rate and separation coefficient of carbon dioxide, the high primary amino content leads to regular arrangement of polymer chains and crystallization regions, thereby reducing the separation efficiency.
The embedded silver nanowires in the PVAm segment disrupt the orderly rearrangement of the PVAm segments, weaken the hydrogen bonding between NH2-NH2, thereby inhibiting the formation of crystallization regions and optimizing the performance of PVAm membrane.
By inhibiting the formation of crystallization zones, the CO2 permeability and selection performance are improved, and the PVAm film performance is optimized.
Smart Images

Figure CN119656895A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of flue gas treatment, and in particular relates to a gas separation membrane and a preparation method and application thereof. Background Art
[0002] With the development of economy and society, the carbon dioxide emissions caused by human activities have been rising year by year, causing serious climate problems. Carbon dioxide emission reduction has become a major issue faced by the world. Membrane separation is a low-energy, modular, and non-secondary pollution carbon dioxide separation technology, showing broad development prospects in the field of carbon dioxide capture.
[0003] The key to membrane separation of carbon dioxide technology lies in membrane materials. The development of membrane materials with both high carbon dioxide permeability and separation coefficient is a current research hotspot. By introducing active groups into polymer membranes, the transmembrane transport of target substances can be promoted, thus breaking through the limitations of traditional organic membranes and achieving high permeability and high selectivity. In addition, the separation components can be reversibly chemically reacted with the carrier to enhance their transfer in the membrane, thereby achieving efficient separation.
[0004] Among many facilitated transfer membrane materials, the permeability selectivity of polyvinylamine (PVAm) membrane is in a leading position and has the possibility of being the first to achieve large-scale industrial application. The group that can transfer carbon dioxide in PVAm membrane is primary amine group (-NH2), and the carbon dioxide separation performance mainly depends on the content of primary amine group and the efficiency of carbon dioxide transfer. Increasing the primary amine content in PVAm membrane is conducive to improving the permeation rate and separation coefficient of carbon dioxide, but too high a primary amino group content will lead to regular arrangement of polymer chains and formation of crystalline areas, which will lead to a decrease in separation efficiency. Therefore, how to avoid the problems caused by too high a primary amino group content is an urgent problem to be solved at this stage. Summary of the invention
[0005] The present invention is based on the inventor's discovery and understanding of the following facts and problems:
[0006] Professor Wang Zhi's research group at Tianjin University used ethylenediamine (EDA) to crosslink PVAm and prepared a PVAm-EDA / PSf composite membrane with a denser structure and more carriers; Norwegian University of Science and Technology The research group has developed a variety of flat composite membranes and hollow fiber composite membranes for separating CO2 / N2 mixed gases. However, despite the excellent performance of this composite membrane in CO2 / N2 separation, the two polymer materials used in this membrane contain polar functional groups, and the interaction of polar functional groups may lead to the formation of crystalline regions, thereby affecting the performance of the membrane. Moreover, due to the interaction of these polar groups, the efficiency of the functional groups will also be reduced.
[0007] Liu Chengcen's research group at Taiyuan University of Technology introduced halloysite nanotubes (HNTs) into polyvinylamine (PVAm) to prepare PVAm-HNTs / PSf mixed matrix membrane. The CO2 permeation rate of the mixed matrix membrane can reach 178GPU, and the CO2 / N2 selectivity is 83. However, due to the complex preparation process and high cost of halloysite nanotubes, it is impossible to achieve industrial mass production.
[0008] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, an embodiment of the present invention provides a gas separation membrane, in which silver nanowires are embedded in PVAm segments, which can effectively disrupt the orderly rearrangement of the PVAm segments, weaken the hydrogen bonding between NH2-NH2 in the PVAm segments, thereby inhibiting the formation of crystalline regions, optimizing the performance of the PVAm membrane, and ultimately achieving the purpose of simultaneously improving the CO2 permeability and selectivity.
[0009] A gas separation membrane according to an embodiment of the present invention includes polyethylene amine and silver nanowires.
[0010] The advantages and technical effects brought by the gas separation membrane of the embodiment of the present invention are as follows: 1. In the embodiment of the present invention, the gas separation membrane adopts polyvinylamine as the membrane-forming material. The primary amino group on the polyvinylamine can attract the carbon dioxide on the flue gas side and transmit it to the other side of the membrane, thereby realizing the separation of carbon dioxide in the flue gas; 2. In the embodiment of the present invention, the silver nanowires loaded in the PVAm can provide adsorption sites, play a physical adsorption role, and improve the separation efficiency of carbon dioxide; 3. In the embodiment of the present invention, the silver nanowires are embedded in the polyvinylamine chain segments, which can effectively disrupt the orderly rearrangement of the PVAm chain segments and weaken the hydrogen bonding between NH2-NH2 in the PVAm chain segments, thereby inhibiting the formation of crystalline regions, realizing the performance optimization of the PVAm membrane, and finally achieving the purpose of simultaneously improving the CO2 permeability and selectivity.
[0011] In some embodiments, the silver nanowires are contained in the gas separation membrane in an amount of 10-70 wt %.
[0012] In some embodiments, the silver nanowires have a length of 5 to 25 μm and a diameter of 20 to 200 nm.
[0013] In some embodiments, the viscosity average molecular weight of the polyvinylamine is 10,000 to 50,000 kDa.
[0014] In some embodiments, the gas separation membrane has a thickness of 300-800 nm.
[0015] The embodiment of the present invention also provides a method for preparing a gas separation membrane, comprising: mixing a silver nanowire solution and a polyvinylamine solution to obtain a mixed solution, scraping the mixed solution on an ultrafiltration membrane to obtain a polyvinylamine-silver nanowire wet film, and performing a drying process to obtain the gas separation membrane.
[0016] In some embodiments, the concentration of the silver nanowire solution is 1 to 10 wt %;
[0017] and / or, the concentration of the polyvinylamine solution is 0.1 to 5 wt%;
[0018] And / or, the content of the silver nanowires in the gas separation membrane is 10-70 wt %.
[0019] In some embodiments, the preparation method of the polyvinylamine solution includes: dissolving N-vinylformamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride in deionized water, heating under nitrogen protection, and performing free radical polymerization to obtain a polyvinylformamide solution; then adding hydrochloric acid solution to the polyvinylformamide solution, heating, and performing a hydrolysis reaction, adding glacial ethanol after the reaction, and drying the product to obtain a polyvinylamine hydrochloride solid; dissolving the polyvinylamine hydrochloride solid in deionized water, adding anion exchange resin for anion exchange, and vacuum filtering to obtain a polyvinylamine solution;
[0020] Preferably, the usage ratio of N-vinylformamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride is (10-40 g): (0.02-0.1 g);
[0021] And / or, the temperature of the free radical polymerization reaction is 50-70° C., and the time of the free radical polymerization reaction is 4-10 hours;
[0022] And / or, the temperature of the hydrolysis reaction is 60-80° C., and the time of the hydrolysis reaction is 2-5 h;
[0023] And / or, the concentration of the hydrochloric acid solution is 30-38 wt %, and the content of hydrochloric acid in the mixed solution of the polyvinyl formamide solution and the hydrochloric acid solution is 10-20 wt %.
[0024] In some embodiments, the preparation method of the silver nanowire solution includes: adding polyvinyl pyrrolidone to ethylene glycol, heating it to react and then cooling it, then adding silver nitrate solution and ferric chloride solution, cooling it after the silver nanowires are formed, centrifuging it with acetone to obtain a precipitate, and using ethanol as a solvent to prepare a silver nanowire solution;
[0025] Preferably, the dosage ratio of polyvinyl pyrrolidone to ethylene glycol is 4 to 20 g / L;
[0026] and / or, the concentration of the silver nitrate solution is 0.01-0.1 mol / L, the concentration of the ferric chloride solution is 0.1-1 mol / L, and the volume ratio of the ethylene glycol, the silver nitrate solution and the ferric chloride solution is (1-10):(1-5):1;
[0027] And / or, the reaction temperature is 140-180° C., and the reaction time is 0.5-2 h.
[0028] The embodiments of the present invention further provide the use of the above-mentioned gas separation membrane or the gas separation membrane prepared by the above-mentioned preparation method in separating carbon dioxide from flue gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a SEM image of the silver nanowires prepared in Example 1;
[0030] Figure 2 is a SEM image of the gas separation membrane prepared in Example 5. DETAILED DESCRIPTION
[0031] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0032] A gas separation membrane according to an embodiment of the present invention includes polyvinylamine (PVAm) and silver nanowires (AgNWs).
[0033] The gas separation membrane of the embodiment of the present invention adopts polyvinylamine as the membrane-forming material. The primary amino group on the polyvinylamine can attract the carbon dioxide on the flue gas side and transmit it to the other side of the membrane, thereby realizing the separation of carbon dioxide in the flue gas; the silver nanowires loaded in the polyvinylamine can provide adsorption sites, play a physical adsorption role, and improve the separation efficiency of carbon dioxide; the silver nanowires are embedded in the polyvinylamine chain segments, which can effectively disrupt the orderly rearrangement of the polyvinylamine chain segments and weaken the hydrogen bonding effect between NH2-NH2 in the polyvinylamine chain segments, thereby inhibiting the formation of crystalline regions, realizing the performance optimization of the polyvinylamine membrane, and ultimately achieving the purpose of simultaneously improving the CO2 permeability and selectivity.
[0034] In some embodiments, preferably, the content of the polyol in the gas separation membrane is 10-70 wt %.
[0035] In the embodiment of the present invention, the content of silver nanowires is optimized, which is conducive to the uniform dispersion of silver nanowires in polyvinylamine without agglomeration, so that the prepared gas separation membrane has a higher gas permeability and separation factor; if the content of silver nanowires is too low, the disruptive effect on the orderly rearrangement of polyvinylamine chain segments is reduced, which will lead to the gas permeability rate of the polyvinylamine membrane being too low; if the content of silver nanowires is too high, the interface compatibility of silver nanowires and polyvinylamine becomes poor, the dispersion effect of silver nanowires in polyvinylamine is reduced, and the separation factor of the polyvinylamine membrane is too low.
[0036] In some embodiments, preferably, the length of the silver nanowire is 5 to 25 μm, and the diameter is 20 to 200 nm. It is understood that the length of the silver nanowire is an average length, such as an average length of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm; the diameter is an average diameter, such as an average diameter of 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm or 200 nm.
[0037] In the embodiment of the present invention, the size of the silver nanowires is optimized. Silver nanowires with appropriate length and diameter can be better dispersed in polyvinylamine and have a better disturbing effect on the orderly rearrangement of the polyvinylamine chain segments. If the length is too long or the diameter is too large, the dispersibility of the silver nanowires in the polyvinylamine solution will deteriorate, and defects will be easily generated after film formation. If the length is too short or the diameter is too small, the disturbing effect on the orderly rearrangement of the polyvinylamine chain segments will deteriorate, thereby reducing the separation efficiency of the gas separation membrane.
[0038] In some embodiments, preferably, the viscosity-average molecular weight of the polyvinylamine is 10,000 to 50,000 kDa.
[0039] In the embodiment of the present invention, the molecular weight of polyvinylamine is preferably selected; if the molecular weight of polyvinylamine is too large, the polymer chain is longer, the fluidity is reduced, the pores in the obtained gas separation membrane are smaller, and the gas permeation rate of the separation membrane is reduced; if the molecular weight of polyvinylamine is too small, the polymer chain is shorter, the pores in the obtained gas separation membrane are larger, and the separation factor of the separation membrane is too low.
[0040] In some embodiments, preferably, the thickness of the gas separation membrane is 300-800 nm.
[0041] In the embodiments of the present invention, the thickness of the gas separation membrane is preferably selected; if the thickness is too large, the resistance to gas transmission is large, which may easily lead to a too low gas permeation rate; if the thickness is too small, the permeation rate increases, but the separation factor is too low.
[0042] The embodiment of the present invention also provides a method for preparing a gas separation membrane, comprising: mixing a silver nanowire solution and a polyvinylamine solution to obtain a mixed solution, coating the mixed solution on an ultrafiltration membrane to obtain a PVAm-AgNWs wet membrane, and performing a drying process to obtain the gas separation membrane.
[0043] In some embodiments, preferably, the concentration of the silver nanowire solution is 1 to 10 wt %;
[0044] and / or, the concentration of the polyvinylamine solution is 0.1 to 5 wt%;
[0045] And / or, the content of the silver nanowires in the gas separation membrane is 10-70 wt %.
[0046] Further preferably, the silver nanowire solution and the polyvinylamine solution are mixed and then subjected to ultrasonic treatment, and the ultrasonic treatment time is 2 to 4 hours.
[0047] In some embodiments, preferably, the preparation method of the polyvinylamine solution comprises: dissolving N-vinylformamide (NVF) and 2,2-azobis(2-methylpropylimidazole) dihydrochloride (AIBA) in deionized water, and heating under nitrogen protection to perform free radical polymerization to obtain a polyvinylformamide (PNVF) solution; then adding hydrochloric acid solution to the polyvinylformamide solution, heating to perform a hydrolysis reaction, adding glacial ethanol after the reaction, and drying the product to obtain a polyvinylamine hydrochloride solid; dissolving the polyvinylamine hydrochloride solid in deionized water, adding anion exchange resin to perform anion exchange, and vacuum filtering to obtain a polyvinylamine solution;
[0048] Further preferably, the usage ratio of N-vinylformamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride is (10-40 g): (0.02-0.1 g);
[0049] And / or, the temperature of the free radical polymerization reaction is 50-70° C., and the time of the free radical polymerization reaction is 4-10 hours;
[0050] And / or, the temperature of the hydrolysis reaction is 60-80° C., and the time of the hydrolysis reaction is 2-5 h;
[0051] And / or, the concentration of the hydrochloric acid solution is 30-38 wt %, and the content of hydrochloric acid in the mixed solution of the polyvinyl formamide solution and the hydrochloric acid solution is 10-20 wt %.
[0052] Further preferably, the amount of the glacial ethanol is 100-5000 mL; and the anion exchange resin is a 717 type strong alkaline anion exchange resin.
[0053] In some embodiments, preferably, the concentration of the polyvinyl formamide (PNVF) solution is 8-12wt%. Further preferably, the concentration of the polyvinyl formamide (PNVF) solution is 10wt%. In order to avoid the adverse effects of the instability of the concentration of the polyvinyl formamide (PNVF) solution on the reaction, the polyvinyl formamide (PNVF) solution is often dried first and then prepared into a solution with a concentration of 8-12wt% with deionized water.
[0054] In some embodiments, preferably, the preparation method of the silver nanowire (AgNWs) solution comprises: adding polyvinyl pyrrolidone (PVP) to ethylene glycol (EG), heating the mixture to react and then cooling the mixture, adding silver nitrate (AgNO3) solution and ferric chloride (FeCl3) solution, cooling the mixture after the silver nanowires are formed, centrifuging the mixture with acetone to obtain a precipitate, and using ethanol as a solvent to prepare a silver nanowire solution;
[0055] Further preferably, the usage ratio of polyvinyl pyrrolidone to ethylene glycol is 4 to 20 g / L;
[0056] and / or, the concentration of the silver nitrate solution is 0.01-0.1 mol / L, the concentration of the ferric chloride solution is 0.1-1 mol / L, and the volume ratio of the ethylene glycol, the silver nitrate solution and the ferric chloride solution is (1-10):(1-5):1;
[0057] And / or, the reaction temperature is 140-180° C., and the reaction time is 0.5-2 h.
[0058] Further preferably, the EG is first preheated in an oil bath at 110-130° C. for 0.5-2 h to remove moisture therein; and / or the cooling includes lowering the temperature to 30° C.
[0059] In the embodiment of the present invention, the preparation process of the method is more controllable and low-cost, and the prepared silver nanowires have good size uniformity and can be uniformly doped in polyethylene amine, thereby reducing the generation of defects during the film formation process.
[0060] In some embodiments, preferably, the centrifugal treatment time is 6 to 12 hours. Further preferably, the method for preparing the silver nanowire (AgNWs) solution further comprises washing the precipitate with ethanol and centrifuging at a speed of 1000-5000 rpm for 3 times, each time for 6 minutes.
[0061] In some embodiments, preferably, the ultrafiltration membrane includes a PSf ultrafiltration membrane, and the surface of the PSf ultrafiltration membrane is cleaned with deionized water before the scraping, and fixed on a flat glass panel after drying. Further preferably, the thickness of the PVAm-AgNWs wet film is 50 to 200 μm, and the drying process is carried out in a constant temperature and humidity chamber at a temperature of 30° C. and a relative humidity of 40%.
[0062] The embodiments of the present invention further provide the use of the above-mentioned gas separation membrane or the gas separation membrane prepared by the above-mentioned preparation method in separating carbon dioxide from flue gas.
[0063] The present invention is described in detail below in conjunction with specific embodiments and drawings.
[0064] Example 1
[0065] (1) Preparation of polyvinylamine solution: 10 g of deionized water was added to a three-necked flask, 40 g of N-vinyl formamide (NVF) was added under stirring, and then 0.057 g of 2,2-azobis(2-methylpropylimidazole) dihydrochloride (AIBA) was added to completely dissolve it; then vacuum was evacuated and filled with nitrogen, and the gas in the reaction system was replaced repeatedly for 3 times. Under nitrogen protection, the temperature was raised to 50°C, and a free radical polymerization reaction was carried out for 8 hours to obtain a polyvinyl formamide (PNVF) solution with a concentration of 10 wt%. Then, a certain amount of concentrated hydrochloric acid solution with a concentration of 36 wt% was added to the polyvinyl formamide (PNVF) solution, so that the content of hydrochloric acid in the mixed solution of the polyvinyl formamide solution and the hydrochloric acid solution was 10 wt%, and the temperature was raised to 70°C for hydrolysis reaction for 3 hours. After the temperature of the reaction system drops to room temperature (25°C), 400 mL of ice ethanol is added to obtain a white solid polyvinylamine hydrochloride precipitate, and the product is vacuum dried at room temperature (25°C) for 24 hours to obtain a polyvinylamine hydrochloride solid product. The polyvinylamine hydrochloride solid product is dissolved in deionized water to prepare a 1.0 wt% solution, and then an excess of 717 type strong basic anion exchange resin is added to the solution for anion exchange, and finally vacuum filtration is performed to obtain a 1.0 wt% PVAm solution.
[0066] (2) Preparation of silver nanowire (AgNWs) solution: 25 mL of ethylene glycol (EG) was placed in a three-necked flask, preheated in a 110°C oil bath for 0.5 to remove the water therein, 0.25 g of polyvinyl pyrrolidone (PVP) was added to the EG, heated to 150°C, reacted for 0.5 h, and then cooled to 30°C; 10 mL of 0.1 mol / L AgNO3 solution and 3 mL of 1 mol / L FeCl3 solution were added, and after AgNWs were gradually formed, it was cooled to 30°C and centrifuged with acetone for 6 h until the precipitate and the supernatant were clearly separated. The precipitate was removed, washed with ethanol, and centrifuged at 3000 rpm for 3 times, each time for 6 min. After obtaining AgNWs, ethanol was used as the solvent to prepare a silver nanowire solution with a content of 5 wt%.
[0067] (3) Preparation of PVAm-AgNWs separation membrane: Add 1 mL of silver nanowire solution to 20 mL of PVAm solution, stir evenly and ultrasonicate for 2 h to obtain a PVAm-AgNWs mixed solution. Wash both sides of the polysulfone PSf ultrafiltration membrane with deionized water, and after the surface is dried, fix the membrane on a flat glass panel. Adjust the distance between the scraper and the surface of the PSf membrane to control the wet coating thickness to 200 μm, and evenly scrape the PVAm-AgNWs solution on the PSf ultrafiltration membrane to obtain a PVAm-AgNWs wet membrane, which is placed in a constant temperature and humidity chamber to dry for 48 h (temperature is 30°C, relative humidity is 40%) to obtain a PVAm-AgNWs gas separation membrane.
[0068] In the gas separation membrane prepared in this embodiment, the viscosity-average molecular weight of polyethylene amine is 49000 kDa, the content of silver nanowires is 12 wt %, the average length of the silver nanowires is 16 μm, the average diameter of the silver nanowires is 50 nm, and the thickness of the gas separation membrane is 500 nm.
[0069] The silver nanowires prepared in this embodiment were characterized by SEM, and the results are shown in the attached Figure 1 As shown, from Figure 1 It can be seen that the prepared silver nanowires have very good size uniformity.
[0070] Example 2
[0071] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (3), the amount of the silver nanowire solution used is 2 mL.
[0072] In the gas separation membrane prepared in this example, the content of silver nanowires is 22 wt %.
[0073] Example 3
[0074] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (3), the amount of the silver nanowire solution used is 5 mL.
[0075] In the gas separation membrane prepared in this example, the content of silver nanowires is 40 wt %.
[0076] Example 4
[0077] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (3), the amount of the silver nanowire solution used is 7 mL.
[0078] In the gas separation membrane prepared in this example, the content of silver nanowires is 49 wt %.
[0079] Example 5
[0080] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (3), the amount of the silver nanowire solution used is 10 mL.
[0081] In the gas separation membrane prepared in this example, the content of silver nanowires is 58 wt %.
[0082] The gas separation membrane prepared in this example was characterized by SEM, and the results are shown in the attached figure. Figure 2 As shown, from Figure 2 It can be seen that the silver nanowires and the polyethylene amine matrix have very good compatibility, and the prepared gas separation membrane has no obvious defects.
[0083] Example 6
[0084] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (3), the amount of the silver nanowire solution used is 15 mL.
[0085] In the gas separation membrane prepared in this example, the content of silver nanowires is 68 wt %.
[0086] Comparative Example 1
[0087] The preparation method of this comparative example is the same as that of Example 1, except that step (2) is eliminated, and step (3) directly uses the PVAm solution prepared in step (1) to be scraped onto the PSf ultrafiltration membrane, the wet coating thickness is controlled to be 200 μm, and then placed in a constant temperature and humidity chamber to dry for 48 hours.
[0088] Performance Testing
[0089] The performance of the PVAm-CDs separation membrane was tested using a separation membrane performance evaluation device (MGPT-Ⅰ type separation membrane performance evaluation device of Dalian Caribona Technology Co., Ltd.). The feed gas first enters the humidification tank to be humidified to saturated humidity, and then enters the membrane pool for testing. The feed gas is a CO2 / N2 mixed gas, the purge gas is helium, the pressure is 0.1MPa, and the permeate side pressure is normal pressure. The permeate side gas enters the gas chromatograph, and the peak area obtained is analyzed to obtain the separation coefficient, and the gas permeation rate is measured by an electronic soap film flowmeter. The test results are shown in Table 1.
[0090] Table 1
[0091]
[0092] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0093] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A gas separation membrane, characterized in that: Includes polyvinylamine and silver nanowires.
2. The gas separation membrane according to claim 1, characterized in that The content of the silver nanowires in the gas separation membrane is 10 to 70 wt %.
3. The gas separation membrane according to claim 1 or 2, characterized in that The length of the silver nanowire is 5 to 25 μm, and the diameter is 20 to 200 nm.
4. The gas separation membrane according to claim 1 or 2, characterized in that: The viscosity average molecular weight of the polyvinylamine is 10000-50000 kDa.
5. The gas separation membrane according to claim 1, characterized in that The thickness of the gas separation membrane is 300-800 nm.
6. A method for preparing a gas separation membrane, characterized in that: include: The silver nanowire solution and the polyvinylamine solution are mixed to obtain a mixed solution, the mixed solution is scraped onto an ultrafiltration membrane to obtain a polyvinylamine-silver nanowire wet membrane, and the mixed solution is dried to obtain the gas separation membrane.
7. The method for preparing a gas separation membrane according to claim 6, characterized in that: The concentration of the silver nanowire solution is 1 to 10 wt %; and / or, the concentration of the polyvinylamine solution is 0.1 to 5 wt %; And / or, the content of the silver nanowires in the gas separation membrane is 10-70 wt %.
8. The method for preparing a gas separation membrane according to claim 6 or 7, characterized in that: The preparation method of the polyvinylamine solution comprises: dissolving N-vinyl formamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride in deionized water, heating under nitrogen protection, and performing free radical polymerization reaction to obtain a polyvinyl formamide solution; then adding a hydrochloric acid solution to the polyvinyl formamide solution, heating, and performing a hydrolysis reaction, adding glacial ethanol after the reaction, and drying the product to obtain a polyvinylamine hydrochloride solid; dissolving the polyvinylamine hydrochloride solid in deionized water, adding anion exchange resin, performing anion exchange, and vacuum filtering to obtain a polyvinylamine solution; Preferably, the usage ratio of N-vinylformamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride is (10-40 g): (0.02-0.1 g); And / or, the temperature of the free radical polymerization reaction is 50 to 70° C., and the time of the free radical polymerization reaction is 4 to 10 hours; And / or, the temperature of the hydrolysis reaction is 60-80° C., and the time of the hydrolysis reaction is 2-5 hours; And / or, the concentration of the hydrochloric acid solution is 30-38 wt %, and the content of hydrochloric acid in the mixed solution of the polyvinyl formamide solution and the hydrochloric acid solution is 10-20 wt %.
9. The method for preparing a gas separation membrane according to claim 6 or 7, characterized in that: The preparation method of the silver nanowire solution comprises: adding polyvinyl pyrrolidone to ethylene glycol, heating it for reaction and then cooling it, adding silver nitrate solution and ferric chloride solution, cooling it after the silver nanowires are formed, centrifuging it with acetone to obtain a precipitate, and using ethanol as a solvent to prepare a silver nanowire solution; Preferably, the dosage ratio of polyvinyl pyrrolidone to ethylene glycol is 4 to 20 g / L; and / or, the concentration of the silver nitrate solution is 0.01-0.1 mol / L, the concentration of the ferric chloride solution is 0.1-1 mol / L, and the volume ratio of the ethylene glycol, the silver nitrate solution and the ferric chloride solution is (1-10):(1-5):1; And / or, the reaction temperature is 140-180° C., and the reaction time is 0.5-2 h.
10. Use of the gas separation membrane according to any one of claims 1 to 5 or the gas separation membrane prepared by the preparation method according to any one of claims 6 to 9 in separating carbon dioxide from flue gas.
Citation Information
Patent Citations
Antimicrobial membrane containing silver nanoparticles
CA2811198A1
Preparation method of high-efficiency compound antibacterial separation membrane
CN101934203A
Metallic nanoparticles stabilised with derivatisied polyethylenimines or polyvinylamines
CN102036773A
Polyvinylamine composite membrane and preparation method and application thereof
CN102961978A
Gas separation membrane based on silver nano particle / polydopamine coated UiO (Universitetet i Oslo)-66-polyether block amide
CN109316984A